Size-modified Poisson–Nernst–Planck approach for modeling a local electrode environment in CO2 electrolysis. Issue 1 (29th November 2022) - Butt, Esaar Naeem; Padding, Johan T.; Hartkamp, Remco
Abstract : A continuum-scale model for CO2 ER is presented, including steric effects of both solute and solvent species along with Frumkin-corrected kinetics. The model gives accurate concentration profiles and experimentally verifiable current density results. Abstract : Electrochemical reduction of CO2 heavily depends on the reaction conditions found near the electrode surface. These local conditions are affected by phenomena such as electric double layer formation and steric effects of the solution species, which in turn impact the passage of CO2 molecules to the catalytic surface. Most models for CO2 reduction ignore these effects, leading to an incomplete understanding of the local electrode environment. In this work, we present a modeling approach consisting of a set of size-modified Poisson–Nernst–Planck equations and the Frumkin interpretation of Tafel kinetics. We introduce a modification to the steric effects inside the transport equations which results in more realistic concentration profiles. We also show how the modification lends the model numerical stability without adopting any separate stabilization technique. The model can replicate experimental current densities and faradaic efficiencies till −1.5 vs. SHE/V of applied electrode potential. We also show the utility of this approach for systems operating at elevated CO2 pressures. Using Frumkin-corrected kinetics gels well with the theoretical understanding of the double layer. Hence, this work provides a sound mechanistic understanding of the CO2 reduction process, from which new insights on key performance controlling parameters can be obtained.